Optimization of the Fins Dimensions for the Absorber with Fins on a Compact Thermal Solar Collector by Entropy Generation Criterion. - ANJORIN, MALAHIMI; ADIHOU, Coffi Wilfrid; HOUNGAN, COMLAN ARISTIDE; AWANTO, CHRISTOPHE; DEGAN, GÉRARD (My University, 2017)
This study present the possibility of adding fins to plate absorbers to improve the performance of the flat plate collector. The objective of this theoretical work is to optimize the dimensions of the fins of the absorbers for a compact solar collector. The performance criterion used is the entropy generation, a global criterion followed by the realization constraint of the black body on the absorber. For that absorber behaves like a black body, the relation between the pitch “y” and the height “z” of fins on the absorber has been determined. The mathematical model of the entropy generation has been determined and simulated according to matlab software. The curves variation of the entropy generation has been drawn according to the pitch “y” of fins of the absorber, the pitch “p” and the height “h” of fins in the working fluid. The results show that the entropy generation is low if the pitch “y” is the lowest, the pitch “p” is raised possible and the height “h” is equal to 0.023 m. the difference between the temperature of the absorber and the one the glass must be low. More this the difference is low, more the optimal speed is low.
Keywords: Fins; solar collector; compact; entropy generation; height; pitch.